Effective Digital Marketing Strategies In Deciding To Buy Halal Products (Empirical Study On New Students Of The Faculty Of Economics, Semarang University) - Kuswardani, DC.; Wibisono, Totok; Setiawan, Wawan; Yani, Tri Endang; Kusnilawati, Nunik (International Journal of Artificial Intelligence Research, 2024)
The research was conducted to produce a formulation of the concept ofDecision to Buy Halal Products in Generation Z with Digital Marketingas a new paradigm of business success perspective, in New Students ofthe Faculty of Economics, University of Semarang The Decision to BuyHalal Products in Generation Z was built through efforts to identify theUse of Social Media, Marketing Influencers and Lifestyle with theUnderstanding of Halal Products as a moderation of the relationshipbetween the Use of Social Media and Lifestyle with the Decision to BuyHalal Products in Generation Z represented by New Students of theFaculty of Economics, University of Semarang. New students of theUniversity of Semarang became the population, while a sample of 175was calculated using the Lemeshow formula. Medelling StructuralEquation (SEM) analysis with the application of the Partial LeastSquare (PLS) program, namely smartPLS.4.0 is used to prove thehypothesis. The results of hypothesis testing show that the Decision toBuy Halal Products is actualized through the Use of Social Media,Influencer Marketing and Lifestyle. The Use of Social Media,Marketing Influencers and Lifestyle directly has a significant effect onthe positive direction of the Decision to Buy Halal Products,Understanding Halal Products is not able to moderate the relationshipbetween the Use of Social Media and Lifestyle in the Decision to BuyHalal Products. The decision to buy Halal products in Generation Z isinfluenced by the Use of Social Media, Marketing Influencer andLifestyle by 53.00%. The research model has a QSquare of 0.2809(>0), which means that the model has strong predictive relevance.Understanding Halal Products in Deciding to Buy Halal Products inGeneration Z.